Features of natural reforestation of clear-cuts in the Ukrainian Carpathians - Бродович , Ю. Р.; Бродович , Р. І.; Кацуляк , Ю. Д.; Сіщук , М. М. (Forestry and Forest Melioration, 2022)
Introduction Improving the reproduction of Ukraine’s forest resources is nowadays an urgent issue. Experience shows that when choosing one or another reforestation method (natural or artificial), priority should be given to silvicultural and typological factors, not just economic ones. Materials and Methods The study was based on the departmental data (projects of natural reforestation for 2022) of 12 state forest enterprises, 107 forestries, and 816 clear-cut plots designed for natural reforestation in the State Forest Fund of Transcarpathian and Chernivtsi regions. We also used the materials of research carried out in previous years by Ukrainian Research Institute of Mountain Forestry. Results The research established that as a result of various types of felling, in the mountainous conditions of the Ukrainian Carpathians, about 8.5 thousand hectares of clear-cuts appear annually. Reforestation of cut areas is carried out by various methods, e.g. by leaving cut areas for natural reforestation, by planting forest stands (partial or continuous), or by combining these methods. The ratio of these methods has changed significantly in recent years. If until the 2000s, the vast majority of cut areas (70–80%) were reforested by planting trees, nowadays most of them are left for natural reforestation. Conclusions Main shortcomings in the design of the natural reforestation method in Ukrainian Transcarpathia occur in the beech and spruce formations of forests after the felling of secondary stands. In particular, there is insufficient white fir amount in the composition of natural regeneration in the case of spruce-fir beech forests and beech forests as well as insufficient English or sessile oak regeneration in oak-hornbeam-beech forests. In the spruce formation, especially after the felling of secondary conifer stands affected by diseases, pests, and windstorms, European spruce is mostly dominant in natural regeneration in cut areas. This, in turn, is a threat of re-emergence of outbreaks and diseases. The natural method of clear-cut reforestation has dominated in the State Forest Fund of Chernivtsi Regional Department of Forest and Hunting Management for a long time due to the wide usage of gradual and reforestation felling. However, a number of deviations from silvicultural and typological requirements were also found here. In particular, it concerns fresh and wet hornbeam oak forests, as well as oak and spruce forests, where a small number (600–800 stems·ha-1) of the second type-forming species, namely common oak, is recorded on cut areas. In the spruce formation of the Bukovyna forests, the study revealed a similar situation to the one in Ukrainian Transcarpathia. The article contains specific proposals regarding the necessity to improve the species composition of self-growth and undergrowth in the analysed forest types and to partially clarify the current regulatory requirements regarding the assessment of natural regeneration on cut areas that are designed for natural reforestation in the Ukrainian Carpathians. 3 Tables, 15 Refs.